1998
DOI: 10.1159/000016863
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Appendiceal Mucoceles

Abstract: Preoperative diagnosis of appendiceal mucoceles is rare. If untreated, one type of mucoceles may rupture producing a potentially fatal entity known as pseudomyxoma peritonei. The importance of diagnosing appendiceal mucoceles is highlighted through a case presentation of a woman who had an incidental finding of mucinous cystadenoma of the appendix during colonoscopic evaluation for occult gastrointestinal bleeding. A detailed review of the medical literature regarding appendiceal mucoceles is presented, with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 13 publications
(14 reference statements)
0
30
0
6
Order By: Relevance
“…A yellowish mucous discharge would be visible from appendiceal orifice during colonoscopy. It is also important for the diagnosis of synchronous or metachronous colon tumor which would be as high as 29% [1,2,7,[13][14][15]24,25] . Colonoscopic examinations on three of our patients revealed indentation in the cecum due to AM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A yellowish mucous discharge would be visible from appendiceal orifice during colonoscopy. It is also important for the diagnosis of synchronous or metachronous colon tumor which would be as high as 29% [1,2,7,[13][14][15]24,25] . Colonoscopic examinations on three of our patients revealed indentation in the cecum due to AM.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous and surgery induced complications of AM include intestinal obstruction, intussusceptions [20,22] , intestinal bleeding [11,13,25] , fistula formation [15,26] , and volvulus [27,28] . The worst complication is pseudomyxoma peritonei, characterized by peritoneal dissemination caused by iatrogenic or spontaneous rupture of the mucocele [5] .…”
Section: Discussionmentioning
confidence: 99%
“…[4] There are 4 histological types: simple mucocele or retention cyst, mucosal hyperplasia, mucinous cystadenoma, and mucinous cystadenocarcinoma. [10,11] Mucinous cystadenocarcinoma is the most frequently seen type after mucinous cystadenoma, and constitutes 11% to 20% of appendiceal mucoceles. A review of the literature revealed some 50 cases of large mucoceles, with a mean diameter of between 13 and 40 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are generally above the age of 50, and it is 4 times more common among women (4). Approximately 25-30% of the patients are symptomatic, and it is incidentally identified during radiological studies, endoscopic examinations or surgery (3,5). The most frequent manifestation among patients with symptomatic appendiceal mucocele is acute or chronic lower right quadrant pain (4).…”
Section: Discussionmentioning
confidence: 99%